From Retreating to Resisting: how Austrian-Turkish women deal with experiences of racism - Hametner, Katharina (Migration Letters, 2014)
Recent European integration discourses are more and more structured by neo-racist topoi based on orientalist markers of difference. In the Austrian debate people of Turkish origins are particularly affected by such ascriptions. They are marked as a group not willing to integrate and culturally not fitting into Austrian society. In this discursive conglomerate women are identified as oppressed victims, lacking education and being in need of help. Using biographical narratives of young Austrian-Turkish women this paper reconstructs four modi of dealing with these discursive ascriptions and experiences of neo-racist othering: retreating and pragmatically reducing ambitions, trivializing racist experiences and assimilating to the mainstream, naming facts and aiming to improve the situation by communication, delegitimizing and ironically transcending racism.